Peeling of convection cells and the generation of sheared flow - Drake, J. F.; Finn, J. M.; Guzdar, P.; Shapiro, V.; Shevchenko, V.; Waelbroeck, F.; Hassam, A. B.; Liu, C. S.; Sagdeev, R. (Physics of fluids. B, Plasma physics, 1992)
A periodic array of convection cells is subject to a ‘‘shear flow’’ instability. The generation of the sheared flow is a consequence of ‘‘peeling’’ of the convection cells. Fluid simulations demonstrate that the efficiency of shear flow generation is high. Implications for understanding poloidal rotation in tokamaks are discussed.